Y2O3 Nanoparticles Caused Bone Tissue Damage by Breaking the Intracellular Phosphate Balance in Bone Marrow Stromal Cells - Gao, Chunyue; Jin, Yi; Jia, Guang; Suo, Xiaomin; Liu, Huifang; Liu, Dandan; Yang, Xinjian; Ge, Kun; Liang, Xing-Jie; Wang, Shuxiang; Zhang, Jinchao (ACS nano, 2019)
Y2O3 nanoparticles (NPs) have become great promising products for numerous applications in nanoscience especially for biomedical application, therefore increasing the probability of human exposure and gaining wide attention in biosecurity. It is well known that rare earth (RE) materials are deposited in the bone and excreted very slowly. Nevertheless, the effect of Y2O3-based NPs on bone metabolism has not been exactly known yet. In the present study, the effects of Y2O3 NPs on bone marrow stromal cells (BMSCs) and bone metabolism in mice after intravenous injection were studied. The results demonstrated that Y2O3 NPs could be taken up into BMSCs and localized in acidifying intracellular lysosomes and underwent dissolution and transformation from Y2O3 to YPO4, which could lead to a break in the intracellular phosphate balance and induce lysosomal- and mitochondrial-dependent apoptosis pathways. Furthermore, after being administered to mice, a higher concentration of yttrium occurred in bone, which caused the apoptosis of bone cells and induced the destruction of bone structure. However, the formation of a YPO4 coating on the surface of Y2O3 NPs by pretreatment of Y2O3 NPs in lysosome-simulated body fluid could observably decrease the toxicity in vivo and in vitro. This study may be useful for practical application of Y2O3 NPs in the biomedical field.